2011
DOI: 10.1186/1479-5876-9-10
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic properties of aged adipose derived mesenchymal stem cells after hypoxic conditioning

Abstract: BackgroundMesenchymal stem cells derived from adipose tissue (ADSC) are multipotent stem cells, originated from the vascular-stromal compartment of fat tissue. ADSC are used as an alternative cell source for many different cell therapies, however in ischemic cardiovascular diseases the therapeutic benefit was modest. One of the reasons could be the use of autologous aged ADSC, which recently were found to have impaired functions. We therefore analysed the effects of age on age markers and angiogenic properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
159
3
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(182 citation statements)
references
References 68 publications
9
159
3
6
Order By: Relevance
“…In analyzing the expression of factors involved in ECM remodeling and vascular cell migration and invasion, we revealed that mRNA levels of uPA, uPAR, and PAI-1 as well as uPAR surface expression were higher in ADSCs from older patients. These results are consistent with those that we previously obtained with ADSCs from young and old mice [42]. Urokinase, a multidomain protein, not only specifically cleaves plasminogen and converts it into plasmin, particularly causing activation of different MMPs, but also initiates intracellular signaling on binding to its receptor on the cell surface and therefore plays multiple roles in vascular remodeling and angiogenesis [52].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In analyzing the expression of factors involved in ECM remodeling and vascular cell migration and invasion, we revealed that mRNA levels of uPA, uPAR, and PAI-1 as well as uPAR surface expression were higher in ADSCs from older patients. These results are consistent with those that we previously obtained with ADSCs from young and old mice [42]. Urokinase, a multidomain protein, not only specifically cleaves plasminogen and converts it into plasmin, particularly causing activation of different MMPs, but also initiates intracellular signaling on binding to its receptor on the cell surface and therefore plays multiple roles in vascular remodeling and angiogenesis [52].…”
Section: Discussionsupporting
confidence: 91%
“…We have previously shown that ADSCs isolated from old mice (18 months), along with acquiring the properties of aged cells (shorter telomeres, higher rate of apoptotic cells, less proliferative capacity, enhanced oxidative damage), have an impaired ability to stimulate blood vessel growth in in vitro and in vivo models of angiogenesis compared with ADSCs from young animals (1-2 months) [42]. In the current study, we analyzed age-associated changes in human ADSCs obtained from both patients without cardiovascular pathology and patients with CAD as a cohort of the most obvious candidates for cell therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, PlGF gene or protein transfer in infarcted mice stimulates angiogenesis in the infarct border and vessel enlargement in the remote myocardium, improving vascular perfusion, cardiomyocyte hypertrophy, and cardiac recovery (Luttun et al 2002;Roncal et al 2008). Unlike systemic treatment with Adipose tissue-derived MSC Viglietto et al 1997;Efimenko et al 2011 Cell types are listed with reported information on inducers of PlGF expression where available. AngII, Angiopoietin II; BMP, bone morphogenic protein; HSC, hepatic stellate cell; IL, interleukin; RPE, retinal pigment epithelial; MSC, mesenchymal stem cell; SMC, smooth muscle cell; TAM, tumor-associated macrophage; TGF, transforming growth factor; TNF, tumor necrosis factor.…”
Section: Plgf a Disease-modifying Candidatementioning
confidence: 99%
“…Bone marrow MSCs from patients aged over 40 years show increased levels of reactive oxygen species (ROS) and nitric oxide (NO) and impaired stress responses [37]. In mice, aged ASCs also exhibit increases in ROS and NO production and a decrease in the antioxidative defense enzyme glutathione peroxide with significant telomere shortening [26]. Our study results using 10% FBS in DMEM as a growth medium imply that ASCs can be cultured until passage 6 for clinical applications.…”
Section: Discussionmentioning
confidence: 82%
“…On the other hand, limited information is currently available regarding the angiogenic potential of aged ASCs [26][27][28]. In the setting of ASC-based therapeutic angiogenesis, clarification of how in vivo and in vitro aging of culturedculture flasks.…”
Section: Introductionmentioning
confidence: 99%